2013
DOI: 10.1007/s00216-013-7288-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioappearance and pharmacokinetics of bioactives upon coffee consumption

Abstract: Habitual consumption of medium amounts of coffee over the whole life-span is hypothesized to reduce the risk to develop diabetes type 2 (DM2) and Alzheimer's disease (AD). To identify putative bioactive coffee-derived metabolites, first, pooled urine from coffee drinkers and non-coffee drinkers were screened by UPLC-HDMS. After statistical data analysis, trigonelline, dimethylxanthines and monomethylxanthines, and ferulic acid conjugates were identified as the major metabolites found after coffee consumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 40 publications
2
92
0
7
Order By: Relevance
“…Such data for tissues are conspicuous by their absence but plasma C max values for metabolites absorbed in the proximal gastrointestinal tract rarely exceed a transient 50 nM for a single bolus dose (unless supplemented) [25,[167][168][169] although 3 ,4 -dimethoxycinnamic acid (ca 0.6 µM after ca two cups of coffee) [170] and 4-hydroxybenzoic acid (2.5 µM after 300 g fresh strawberries) [22] are notable exceptions. In contrast, as discussed above, for those catabolites derived from multiple substrates, and especially those associated with commodities consumed repeatedly at short intervals during the day, a higher C max is to be expected, in some cases exceeding 1 µM.…”
Section: Effects Of Catabolitesmentioning
confidence: 99%
“…Such data for tissues are conspicuous by their absence but plasma C max values for metabolites absorbed in the proximal gastrointestinal tract rarely exceed a transient 50 nM for a single bolus dose (unless supplemented) [25,[167][168][169] although 3 ,4 -dimethoxycinnamic acid (ca 0.6 µM after ca two cups of coffee) [170] and 4-hydroxybenzoic acid (2.5 µM after 300 g fresh strawberries) [22] are notable exceptions. In contrast, as discussed above, for those catabolites derived from multiple substrates, and especially those associated with commodities consumed repeatedly at short intervals during the day, a higher C max is to be expected, in some cases exceeding 1 µM.…”
Section: Effects Of Catabolitesmentioning
confidence: 99%
“…We found that caffeinated coffee was associated with serum catechol sulfate, but not urinary catechol sulfate. Catechol, a derivative of coffee processing, is conjugated to catechol sulfate to facilitate absorption (65,66). Conjugated polyphenol metabolites generally are eliminated in feces (61).…”
Section: Tablementioning
confidence: 99%
“…57 On the contrary, concentrations of at least 100 µM were necessary to inhibit the expression of TRAP-and ADPinduced P-selectin by the early metabolites CA and FA, and 5-CQA, respectively, 42,58 while the 12 results of this study showed a significant decrease of ADP-induced P-selectin expression at noticeably lower concentrations (20, 10 and 1 µM for CA, FA and 5-CQA, respectively), indicating that the colonic metabolites may have an even stronger effect on platelet function than their phenolic precursors. Early metabolites from CGA appear at 1 -2 h after coffee intake, and have a short life time of approximately 30 min, 21,59 whereas DHCA and DHFA appear in the circulation 5 -10 h after consumption and their life time is between 0.7 and 2.1 h. 19 A longer circulation time of colonic metabolites, together their higher effect on platelet function, suggest that these colonic metabolites may be the main contributors to the beneficial effect of CGA-rich foods on human platelet function. The differences in efficacy could relate to their molecular structure.…”
Section: Effect On Fibrinogen Bindingmentioning
confidence: 99%